LAND CONSOLIDATION AS A LAND MANAGEMENT TOOL FOR PRESERVING NATURAL LANDSCAPES - Stoiko , Н.; Cherechon , О. В.; Cherechon, О.І. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
In Ukraine, a significant environmental challenge is the considerable loss of biological and landscape diversity, driven by intense anthropogenic pressure and military activities. To promote the conservation of habitats and landscapes within the framework of sustainable development, several regulatory and legal measures have been enacted aimed at expanding areas of land covered by natural vegetation. Effective land management plays a crucial role in this context, as it facilitates the implementation of strategies designed to preserve natural landscapes, protect land from degradation, and mitigate other adverse phenomena. One effective tool for implementing such strategies is land consolidation, which involves restructuring land ownership and plots to optimize land use and support the ecological sustainability of various areas. This article explores the connection between land consolidation and the design of ecological network territories on privately owned agricultural land exhibiting signs of degradation or low productivity. Using the Rozvadiv territorial community in Lviv region as a case study, two scenarios for designing ecological (Emerald) network territories have been proposed, using majority-based land consolidation and mandatory land consolidation. This dual approach allows for both voluntary and mandatory land exchanges. However, these consolidation forms necessitate reliable government institutions and an appropriate legal framework to ensure the protection of the rights of landowners and users involved in the land redistribution process. A key requirement for mandatory land consolidation is the availability of reserve land (land bank). Moreover, land consolidation must involve consultations with all stakeholders. The authors emphasize that incorporating natural land conservation and restoration practices into the land consolidation process is vital for achieving sustainable land management and ensuring the long-term preservation of ecosystems.